Bourne, Britain And The Great War, 1914-1914 - Salevouris, Michael (Teaching History: A Journal of Methods, 1992)
"War," said Thomas Paine, "involves in its progress such a train of unforseen and unsupposed circumstances that no human wisdom can calculate the end." History is replete with examples of wars that didn’t exactly go as planners planned, but one conflict above all, the "Great War" of 1914-1918, has been responsible for our contemporary fear of the "unforseen and unsupposed circumstances" of war. The short, heroic, victorious war that most Europeans foresaw in August, 1914, became an unimaginable tragedy that buried a generation in the mud of the western front. It is, therefore, not surprising that books on World War I continue to flow from the presses.